Civil War time : temporality & identity in America, 1861-1865 - Wells, Cheryl A., 1972- (University of Georgia Press, 2005)
"In antebellum America, both North and South emerged as modernizing, capitalist societies. Work bells, clock towers, and personal timepieces increasingly instilled discipline on one's day, which already was ordered by religious custom and nature's rhythms. The Civil War changed that, argues Cheryl A. Wells, by overriding antebellum schedules and playing havoc with people's perception and use of time. For those closest to the fighting, the war's effect on time included disrupted patterns of sleep, extended hours of work, conflated hours of leisure, indefinite prison sentences, challenges to the gender order, and desecration of the Sabbath."